Regulated cell death in chronic kidney disease: current evidence and future clinical perspectives - Giuliani, Kurt T. K.; Adams, Benjamin C.; Healy, Helen G.; Kassianos, Andrew J. (Frontiers in Cell and Developmental Biology, 2024)
Chronic kidney disease (CKD) is the progressive loss of kidney function/structure over a period of at least 3 months. It is characterised histologically by the triad of cell loss, inflammation and fibrosis. This literature review focuses on the forms of cell death that trigger downstream inflammation and fibrosis, collectively called regulated cell death (RCD) pathways. Discrete forms of RCD have emerged as central mediators of CKD pathology. In particular, pathways of regulated necrosis – including mitochondrial permeability transition pore (mPTP)-mediated necrosis, necroptosis, ferroptosis and pyroptosis – have been shown to mediate kidney pathology directly or through the release of danger signals that trigger a pro-inflammatory response, further amplifying tissue injury in a cellular process called necroinflammation. Despite accumulating evidence in pre-clinical models, no clinical studies have yet targeted these RCD modes in human CKD. The review summarizes recent advances in our understanding of RCD pathways in CKD, looks at inter-relations between the pathways (with the emphasis on propagation of death signals) and the evidence for therapeutic targeting of molecules in the RCD pathways to prevent or treat CKD.